Advanced simulation methods for ESD protection development - Esmark, Kai
Simulation Methods for ESD Protection Development looks at the integration of new techniques into a comprehensive development flow, which is now available due advances made in the field during the recent years. These findings allow for an early, stable ESD concept at a very early stage of the technology development, which is essential now development cycles have been reduced. The book also offers ways of increasing the optimization and control of the technology concerning performance. Thus making the process more cost effective and increasingly efficient This title provides a guide through the latest research and technology presenting the ESD protection development methodology. This is based on a combination of process, device and circuit stimulation, and addresses the optimization of the industry critical issue, reduced development cycles. Written to address the needs of the ESD engineer, this text is required reading by all industry practitioners and researchers and students within this field. The FIRST Extensive overview on the subject of ESD simulation Addresses the industry critical issue of reduced development cycles, and provides solutions Presents the latest research in the field with high practical relevance and its results.